2014
DOI: 10.1111/febs.12867
|View full text |Cite
|
Sign up to set email alerts
|

Structure of RPA32 bound to the N‐terminus of SMARCAL1 redefines the binding interface between RPA32 and its interacting proteins

Abstract: , Tipin, UNG2 and XPA. We have solved the high-resolution crystal structure of RPA32 C-terminal domain (RPA32C) in complex with a 26-amino-acid peptide derived from the N-terminus of SMARCAL1 (SMARCAL1N). The RPA32C-SMARCAL1N structure reveals a 1 : 1 binding stoichiometry and displays a well-ordered binding interface. SMARCAL1N adopts a long a-helical conformation with the highly conserved 11 residues aligned on one face of the a-helix showing extensive interactions with the RPA32C domain. Extensive mutagenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 39 publications
6
23
1
Order By: Relevance
“…3 A). This is somewhat higher than the measured K d of 2.9 mM for the interaction of unlabeled SMARCAL peptide with the isolated WH domain (32), although the labeled peptide had sufficient affinity for our competition experiments. SMARCAL peptide was next equilibrated with RPA, then displaced with full-length UNG2 to obtain an IC 50 , from which we calculated a K d of 3.2 mM for the UNG2-RPA interaction (Fig.…”
Section: Ung2-rpa Binding and Ternary Complex Formationcontrasting
confidence: 56%
See 1 more Smart Citation
“…3 A). This is somewhat higher than the measured K d of 2.9 mM for the interaction of unlabeled SMARCAL peptide with the isolated WH domain (32), although the labeled peptide had sufficient affinity for our competition experiments. SMARCAL peptide was next equilibrated with RPA, then displaced with full-length UNG2 to obtain an IC 50 , from which we calculated a K d of 3.2 mM for the UNG2-RPA interaction (Fig.…”
Section: Ung2-rpa Binding and Ternary Complex Formationcontrasting
confidence: 56%
“…2 A) (3,6). The UNG2 binding site on the RPA32 WH domain is shared with several DNA replication/repair proteins (29)(30)(31)(32), and we synthesized a fluorescently labeled peptide called SMARCAL that also binds to this common site (32). With a fluorescence anisotropy assay, we first determined a K d of 12.3 mM for the SMARCAL peptide interaction with RPA (Fig.…”
Section: Ung2-rpa Binding and Ternary Complex Formationmentioning
confidence: 99%
“…The conserved helicase motifs are the characteristic features of the ATP-dependent chromatin remodeling proteins. Though the structural information for the N-terminus region of SMARCAL1 interacting with replication protein A-32 (RPA32), the single-strand DNA binding protein present in eukaryotic cells, is known, 20 crystal structure of the C-terminus region containing the helicase motifs has not yet been solved. In the absence of structural information for the ATPase domain of SMARCAL1, mutational analysis of ADAAD had been attempted in order to understand the contribution of the helicase motifs to DNA-dependent ATPase activity and to the pathophysiology.…”
Section: The Conserved Helicase Motifs Of Smarcal1mentioning
confidence: 99%
“…20 SMARCAL1 peptide adopts an α-helical structure with side chains of K12, N16, R17, and R23 forming hydrogen bonds with V259 of RPA32. 20 Biochemical techniques such as isothermal titration calorimetry have shown that the N-terminal RPA binding motif of SMARCAL1 binds RPA with a dissociation constant (K d ) of 2.46 μM. 52 The circular dichroism (CD) data showed an increase in the α-helical content of RPA on binding SMARCAL1, suggesting that conformational alterations are induced in RPA on interaction with SMARCAL1.…”
Section: Smarcal1 Stabilizes Stalled Replication Forksmentioning
confidence: 99%
“…It is also possible that multiple Marcal1 molecules bind the nascent DNA and the presence of any wild-type protein is sufficient to rescue the Marcal1 K275M phenotype. Recent work on the RPA-SMARCAL1 interface has shown that SMARCAL1 binds to the C-terminal region of RPA32 with 1:1 stoichiometry (Bhat et al 2014;Xie et al 2014) and it is likely that many molecules of Marcal1 bind the RPA-coated nascent DNA, allowing for multiple complementarity searches to occur simultaneously. Studies have revealed a similar mechanism for homology searching by Rad51-coated ssDNA (Wright and Heyer 2014;Qi and Greene 2016).…”
Section: Atp Binding Is Required For Marcal1 Activity During Sdsamentioning
confidence: 99%